CADM1 and MAL promoter methylation levels in hrHPV‐positive cervical scrapes increase proportional to degree and duration of underlying cervical disease. Issue 6 (4th April 2013) - Bierkens, Mariska; Hesselink, Albertus T.; Meijer, Chris J.L.M.; Heideman, Daniëlle A.M.; Wisman, G. Bea A.; van der, Ate G.J.; Snijders, Peter J.F.; Steenbergen, Renske D.M.
<x xml:space="preserve">Abstract</x> Combined detection of cell adhesion molecule 1 (CADM1) and T‐lymphocyte maturation‐associated protein (MAL) promoter methylation in cervical scrapes is a promising triage strategy for high‐risk human papillomavirus (hrHPV)‐positive women. Here, CADM1 and MAL DNA methylation levels were analysed in cervical scrapes of hrHPV‐positive women with no underlying high‐grade disease, high‐grade cervical intraepithelial neoplasia (CIN) and cervical cancer. CADM1 and MAL methylation levels in scrapes were first related to CIN‐grade of the corresponding biopsy and second to CIN‐grade stratified by the presence of 'normal' or 'abnormal' cytology as present in the accompanying scrape preceding the cervical biopsy. The scrapes included 167 women with ≤CIN1, 54 with CIN2/3 and 44 with carcinoma. In a separate series of hrHPV‐positive scrapes of women with CIN2/3 (n = 48), methylation levels were related to duration of preceding hrHPV infection (PHI; <5 and ≥5 years). Methylation levels were determined by quantitative methylation‐specific PCR and normal cytology scrapes of hrHPV‐positive women with histologically ≤CIN1 served as reference. CADM1 and MAL methylation levels increased proportional to severity of the underlying lesion, showing an increase of 5.3‐ and 6.2‐fold in CIN2/3, respectively, and 143.5‐ and 454.9‐fold in carcinomas, respectively, compared to the reference. Methylation levels were also elevated in CIN2/3 with a longer duration of PHI (i.e. 11.5‐ and 13.6‐fold, respectively). Moreover, per histological category, methylation levels were higher in accompanying scrapes with abnormal cytology than in scrapes with normal cytology. Concluding, CADM1 and MAL promoter methylation levels in hrHPV‐positive cervical scrapes are related to the degree and duration of underlying cervical disease and markedly increased in cervical cancer.